La construcción discursiva de un genocidio en Colombia: una aproximación a la versión de las Fuerzas Militares en el caso de la Unión Patriótica (2013)
In the 80s, during the political and social conflict between the guerrillas and the Colombian state, the Patriotic Union (Unión Patriótica) grew and consolidated as a negotiated alternative different from traditional two parties. It also started to improve in the electoral landscape all over Colombia. Simultaneously, this was the beginning of one of the biggest waves of political violence and repression thatwould result in the extermination of this group. In the context of this genocide, the Armed Forces played an important role, by action and omission, and helped to construct a political discourse that described the UP as an enemy and consequently, they contributed to legitimize their annihilation.